Rationale for Combining Bispecific T Cell Activating Antibodies With Checkpoint Blockade for Cancer Therapy - Kobold, Sebastian; Pantelyushin, Stanislav; Rataj, Felicitas; vom Berg, Johannes (Frontiers in Oncology, 2018)
T cells have been established as core effectors for cancer therapy; this has moved the focus of therapeutic endeavors to effectively enhance or restore T cell tumoricidal activity rather than directly target cancer cells. Both antibodies targeting the checkpoint inhibitory molecules programmed death receptor 1 (PD-1), PD- ligand 1 (PD-L1) and cytotoxic lymphocyte activated antigen 4 (CTLA-4), as well as bispecific antibodies targeting CD3 and CD19 are now part of the standard of care. In particular, antibodies to checkpoint molecules have gained broad approval in a number of solid tumor indications, such as melanoma or non-small cell lung cancer based on their unparalleled efficacy. In contrast, the efficacy of bispecific antibody-derivatives is much more limited and evidence is emerging that their activity is regulated through diverse checkpoint molecules. In either case, both types of compounds have their limitations and most patients will not benefit from them in the long run. A major aspect under investigation is the lack of baseline antigen-specific T cells in certain patient groups, which is thought to render responses to checkpoint inhibition less likely. On the other hand, bispecific antibodies are also restricted by induced T cell anergy. Based on these considerations, combination of bispecific antibody mediated on-target T cell activation and reversal of anergy bears high promise. Here, we will review current evidence for such combinatorial approaches, as well as ongoing clinical investigations in this area. We will also discuss potential evidence-driven future avenues for testing.